2009
DOI: 10.1007/s10653-008-9244-z
|View full text |Cite
|
Sign up to set email alerts
|

Watershed land use as a determinant of metal concentrations in freshwater systems

Abstract: Concentrations of Fe, Mn, Cu, dissolved organic matter (DOM), and pH were synthesized from 30 publications to determine the factors regulating concentrations and behavior of metals in freshwater systems. Results from the review suggest that contrasting watershed land use can directly (erosion and runoff) and indirectly (in-lake processes including metal-DOM-pH interactions) affect the metal concentrations in freshwater systems. Among the watershed land uses considered here, concentrations of Fe, Mn, and Cu wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 69 publications
0
21
1
Order By: Relevance
“…Specifically, Fe, Mn and Cu were consistently high in urban watersheds [Fe (12-58 g/L), Mn (0.20-30 g/L) and Cu (0.4-15 g/L)], with only streams draining mining areas having higher concentrations (Das et al 2009) [109]. Additionally, metal concentrations were inversely correlated with pH indicating that at low pH levels, metal solubility increases and metal particles become more mobile.…”
Section: Urbanization Effects On Water Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, Fe, Mn and Cu were consistently high in urban watersheds [Fe (12-58 g/L), Mn (0.20-30 g/L) and Cu (0.4-15 g/L)], with only streams draining mining areas having higher concentrations (Das et al 2009) [109]. Additionally, metal concentrations were inversely correlated with pH indicating that at low pH levels, metal solubility increases and metal particles become more mobile.…”
Section: Urbanization Effects On Water Qualitymentioning
confidence: 97%
“…In a review of 135 observations from a wide range of aquatic ecosystems, watershed land use was shown to directly (erosion and runoff) and indirectly (pH driven metal-DOM interactions) affect metal concentrations in freshwaters [109]. Specifically, Fe, Mn and Cu were consistently high in urban watersheds [Fe (12-58 g/L), Mn (0.20-30 g/L) and Cu (0.4-15 g/L)], with only streams draining mining areas having higher concentrations (Das et al 2009) [109].…”
Section: Urbanization Effects On Water Qualitymentioning
confidence: 99%
“…This study's results appear to be similar to the Christian et al (2011) study in that urbanization tends to decrease iron concentrations. By contrast Paul & Meyer (2001) observed that urbanization increases iron concentrations; this was also true for most of the 30 studies included in Das et al (2009). Maybe in this area water acidity is more important than land use.…”
Section: Resultsmentioning
confidence: 94%
“…Maybe in this area water acidity is more important than land use. Das et al (2009) noted that increases in acidity tends to increase iron concentrations in lakes, so maybe this is happening to the set of streams in the study area. In this area both of these landscapes are largely tree covered-forest landscapes, which in this case is pine and hardwood mix forest (Smith, 1999).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation